IMPLEMENTASI PROGRAM SABTU BUDAYA SEBAGAI PENGUATAN CIVIC CULTURE - SAJIDA, DEANA; HERIANTO, EDY; BASARIAH, BASARIAH; SAWALUDIN, SAWALUDIN (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
The Culture Saturday program is a co-curricular activity used in schools to promote culture-based learning. The purpose of this study is to explain the Saturday Culture programme's implementation as a reinforcement of Civic Culture, which may be both helpful and difficult, as well as the influence it has. This research takes a qualitative approach to case study research. Data collecting strategies include observation, interviews, and documenting. Results can be obtained from the data, among other things. (1) the form of implementation of the Saturday Culture program as a strengthening of Civic Culture in the State Primary School 1 Masbagik is Gatra Gatra Gymnastics, Theatre or Drama Activities, Creation Dance Activities, and Classroom Cleaning and Environmental Activities; (2) the supporting factors, including the competence of teachers to implement the Saturday Cultural program, the support and cooperation between teachers and staff, the availability of the venue of The challenges include the guidance of the school's Saturday Culture program, the participation of some students and teachers in the implementation of the Saturday Culture programme, and (3) the impact on the academic field on the learning of pupils and non-academic pupils on the discipline, activity, participation, or controversy of the pupils in the conduct of the cultural Saturday program. ABSTRAKBudaya yang Program Sabtu adalah kegiatan co-curricular yang digunakan di sekolah untuk mempromosikan pembelajaran berbasis budaya. Tujuan dari studi ini adalah untuk menjelaskan implementasi program Saturday Culture sebagai penguatan budaya sipil, yang dapat bermanfaat dan sulit, serta pengaruhnya. Penelitian ini mengambil pendekatan kualitatif untuk penelitian studi kasus. Strategi pengumpulan data termasuk pengamatan, wawancara, dan dokumentasi. Hasil dapat diperoleh dari data, antara lain. (1) bentuk implementasi program Budaya Sabtu sebagai penguatan Budaya Sipil di Sekolah Dasar Negara 1 Masbagik adalah Gimnastik Gatra Gatra, Aktivitas Teater atau Drama, Kegiatan Tarian Kreatif, dan Kelas Pembersihan dan Kegiatan Lingkungan; (2) faktor-faktor pendukung, termasuk kompetensi guru untuk menerapkan program Kebudayaan Sabtu, dukungan dan kerjasama antara guru dan staf, ketersediaan lokasi Tantangan-tantangan tersebut meliputi bimbingan program Budaya Sabtu sekolah, partisipasi beberapa siswa dan guru dalam implementasi program Kebudayaan Sabtu, dan (3) dampak pada bidang akademik pada pembelajaran siswa dan siswa non-akademik pada disiplin, aktivitas, keterlibatan, atau kontroversi siswa dalam pengelolaan program budaya Sabtu.